Voltammetric oxidation of potassium thiocyanate using ErBa2Cu3O7 modified glassy carbon electrode. - Mohammed Zidan,; Tan, Wee Tee; Alaghbari, Elyas Sadeq; Ahmad, Mansor; Shameli, Kamyar (Electrochemical Science Group, 2013)
The electrochemical analysis of ErBa2Cu3O7 (ErBCO) superconductor materials, adhered at a glassy carbon electrode surface placed in an aqueous media has been investigated by cyclic voltammetry technique. Voltammetric determination of the oxidation of Thiocyanate in 0.1 M NH4Cl electrolyte solution by solid phase voltammetry has shown the effect of copper–thiocyanate complexes. Observation revealed a high peak of ErBCO appears at 220 mV vs Ag/AgCl when there is an absence of thiocyanate, while in the presence of thiocyanate, peak current increases by 3.1. The voltammetric response of the ErBCO was found to depend greatly on the scan rate and pH. From CC studies, the amount of charge, Q that was present on the electrode surface is 5.513 µC/cm. The diffusion coefficient,D, value for the copper–thiocyanate complexes was determined to be 7.48x10-05 cm2/s.